E-022 In vivo endothelialization of VEGF-coated stents in a rabbit model. (4th August 2020) - Panchendrabose, K; Har, B; Mitha, A
Abstract : Introduction: Implantation of cerebral stents are used in several disease conditions. Although stenting procedures offer many benefits, metal stents can elicit acute/subacute thrombosis and increase the chance of stroke. The risk of in-stent thrombus formation significantly decreases after formation of an endothelial cell layer over the stent, which typically takes several weeks to occur. One potential way to reduce the formation of thrombus is through biologic modifications that hasten endothelialization. In past studies, vascular endothelial growth factor (VEGF) has been shown to facilitate the recruitment and proliferation of cells that leads to endothelialization. Methods: In this study, VEGF was coated onto Solitaire stents using polylactic-co-glycolic acid (PLGA). Coated stents were deployed into the infrarenal abdominal aorta of New Zealand White rabbits for 72 hours (n=5) (72h VEGF group) and compared to uncoated stents at 72 hours (n=3) (72h Control group) and seven days (n=3) (7d Control group). Optical coherence tomography (OCT) was performed through the stented portion of the vessel, and representative images taken every five millimetres were used for analysis. Images were analyzed for neointimal area (stent area – lumen area), neointimal ratio ([stent area – lumen area]/stent area), minimal and maximal neointima thickness, stent-strut neointima coverage ratio (number of struts covered by a neointimal layer over the total number of struts), as well as thrombus area formation. The analysis was performed by a cardiologist with clinical expertise in OCT imaging, who was also blinded to group allocation. Results: Post-deployment digital subtraction angiography demonstrated that VEGF-coated stents were deployed similar to uncoated stents, and without any obvious acute thrombus formation. Using two-tailed unpaired t -tests, the 72h VEGF group showed significantly higher ( p <0.01) neointimal area and neointimal ratio compared to 72h Control group. The minimal neointimal thickness of 72h VEGF group was significantly higher ( p <0.05) than the 72h Control group, but not statistically different from the 7d Control group. There was a trend toward decreased thrombus formation in 72h VEGF group versus the 72h Controls ( p =0.07). The 7d Controls had significantly higher stent-strut neointimal coverage ratio, neointimal area, neointimal ratio and maximum neointimal thickness compared to the 72h VEGF group ( p <0.05) and 72h Control group ( p <0.05). Conclusion: VEGF-coated stents are a promising biomodification to reduce secondary complications that may occur in the initial days following the procedure. Disclosures: K. Panchendrabose: None. B. Har: 3; C; Abbot. A. Mitha: 1; C; Stryker Neurovascular. 2; C; Microvention Inc., Cerus Endovascular, Stryker Corporation. 4; C; Fluid Biotech Inc.